SỰ GIA TĂNG TỶ LỆ XẢY THAI TỰ NHIÊN VÀ TỬ VONG TRẺ EM Ở PHỤ NỮ DI CƯ VÀO CÁC VÙNG BỊ RẢI CHẤT ĐỘC DA CAM / DIOXIN - Ngô, Thanh Nam; Lê, Duy Cương; D. A. , Belov; N. V., Umnova (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
AN INCREASE OF SPONTANEOUS ABORTION AND CHILD MORTALITY RATES IN WOMEN IMMIGRATED TO AGENT ORANGE SPRAYED REGIONS During the period from 2007 to 2010, the reproductive disorders of women migrated from the North to Agent Orange sprayed regions of Tay Nguyen Highland and the health status of their F1 generation were investigated. The subjects aged 35- 54 were divided into 2 groups: The high-risk exposure group (n = 353) consisting of the women who were younger than 21 years and migrated to the sprayed regions before 1990; the low-risk exposure group (n = 477) consisting of the women aged 21 or older and have migrated since 1990. The controls (n = 1116) were the women living in the immigrant’s homelands in the North. The study results showed that: Spontaneous abortion/ stillbirth rates and mortalities among F1 generation of the exposure groups were higher than that of the controls, but no high Dioxin level was found in all environmental and food samples collected from the studied regions. Dioxin levels in environment and human tissues are now being monitored in order to obtain the actual level of exposure to Agent Orange.